2009
DOI: 10.1038/nature08206
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin kinase couples TNF receptor 1 to NADPH oxidase

Abstract: Reactive oxygen species (ROS) produced by NADPH oxidase function as defence and signalling molecules related to innate immunity and various cellular responses. The activation of NADPH oxidase in response to plasma membrane receptor activation depends on the phosphorylation of cytoplasmic oxidase subunits, their translocation to membranes and the assembly of all NADPH oxidase components. Tumour necrosis factor (TNF) is a prominent stimulus of ROS production, but the molecular mechanisms by which TNF activates N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 27 publications
4
181
1
4
Order By: Relevance
“…A recent study reported that ROS generation requires recruitment of riboflavin kinase (RFK) and the NADPH oxidases Nox1 and Nox2 to TNFR1. 26,28 We found that specific repression of components of the NADPH oxidase complex (RFK, Nox1, and p22phox) by RNAi did not affect death induced by TNF or TNF þ BV6, but repression of NADH dehydrogenase (ubiquinone) 1 beta subcomplex 8 (NDUFB8) (subunit of mitochondrial complex I) strongly attenuated it (Figure 5f and data not shown). Our results therefore indicate that, in the absence of cIAP1, TNF-induced necrosis in L929 cells requires RIP1/3-mediated mitochondrial ROS production.…”
Section: Resultsmentioning
confidence: 89%
“…A recent study reported that ROS generation requires recruitment of riboflavin kinase (RFK) and the NADPH oxidases Nox1 and Nox2 to TNFR1. 26,28 We found that specific repression of components of the NADPH oxidase complex (RFK, Nox1, and p22phox) by RNAi did not affect death induced by TNF or TNF þ BV6, but repression of NADH dehydrogenase (ubiquinone) 1 beta subcomplex 8 (NDUFB8) (subunit of mitochondrial complex I) strongly attenuated it (Figure 5f and data not shown). Our results therefore indicate that, in the absence of cIAP1, TNF-induced necrosis in L929 cells requires RIP1/3-mediated mitochondrial ROS production.…”
Section: Resultsmentioning
confidence: 89%
“…Although the mitochondrial electron transport chain is the main mechanism of ROS generation, oxygen radicals can also be produced by other enzymatic sources like NADPH oxidase, xanthine oxidase, and NOS. It has been shown previously that TNF␣ stimulates ROS generation by the NADP oxidase 1 (Nox1) system at the cell membrane (52,53) and that GCs increase oxidative stress by activating xanthine oxidase (54,55). Whether p66…”
Section: Discussionmentioning
confidence: 99%
“…Similar as in replicational stress, linking p53 to NF-kB signaling allows antiapoptotic gene expression in cells where the tumor suppressor can execute apoptosis if necessary. Such situations arise, for example, when TNF promotes inflammation-related tumorigenesis by NF-kB activation (Pikarsky et al, 2004;Hayashi et al, 2007) or by TNF-mediated induction of reactive oxygen species bearing mutagenic potential (Yan et al, 2006;Li et al, 2007;Yazdanpanah et al, 2009). Of note, p53-positive cells can protect themselves from such cyto-and genotoxic molecules by inducing MnSOD, an antioxidizing enzyme known to balance TNF signaling (Gilmore and Herscovitch, 2006).…”
Section: Control Of Activated Nf-jb By P53mentioning
confidence: 99%